Manajemen Pelaporan Pendapatan dan Pemilihan Metode Akuntansi pada Penawaran Saham Perdana di Bursa Efek Jakarta - Handriyono (2001)
Asymmetry information about corporate condition in initial public offerings creates motivation to the corporate management to show to the potential onvestors that the performance of the corpora=ation is good. To the investors, the only source of information to value the performance of the issuing firms is by examining the company financial report, especially its income or profits. The improvement of profit is expected to be followed by the improvement of stock price. Consequently, it is reasonable for the management to show their company financial performance especially their income. In other words, the management of corporation has the opportunity to manage financial report in their best interest by managing their financial information or by utilizing accounting methods to increase the reported income. Earning management can be conducted by performing accruals management. Accruals management is possible to be performed because in initial public offerings there is no public information prior to the public issue. Thus, investors must conduct analysis to examine wheter there is accruals management in the company financial reports. Tehere are many factors affecting the desire of the owners of the company to manage the accounting information. Empirical evidence has indicated that there are at least five factors to be related with earnings management, namely company size, growth of total assets, financial leverage, the proportion of retained ownership, and the underwriter prestige. This study uses 34 company as the sample in the manufacturing industry that went public during 1995 to June 1997 in the Jakarta Stock Exchange. The results of the analysis using total accruals approach, it was found that there is no evidence of earnings management that the issuers of the issuing company manage inancial report in the period one year and two years before going public. This is shown by the fact that there is no significant finding using. The Wilcoxon Signed Rank test in the period of one year prior to going public with Z-value of-0,658 with the p-value of 0,510. For the period of two years prior to go public the Z-value is -1,222 and the p-value is 0,222, which are statistically insignificant. The results of the multivariate analysis using the ordinary least square (OLS regression) suggest that only the size of the company and the growth of total assets have the significant relationship with accruals management during the period prior to going public. The other explanatory variables are found to be not significant.